A Review on Requisite Generic Attributes for Engineering Graduates - Meenakshi, S.; Rath, Amiya Kumar; Mohanty, Seemita (Journal of Engineering Education Transformations, 2015)
Engineering education today has seen enormous growth and development in terms of the quality of education and the deliverables. The profession is experiencing major changes in knowledge, equipment, systems and management in order to achieve higher standards in a competitive world. Consequently, engineering firms continuously need engineers with strong technical knowledge, in addition to being well-equipped with employability skills. In order to face new challenges, new opportunities and ever challenging circumstances, new engineers have to continually adapt and upgrade necessary skills such as self-learning, problem solving and other personal skills that can be applied in different situations. Apart from the technical knowhow’s and show-how’s, they also need the requisite interpersonal skills to thrive in the field in the long term. In this paper, we review the package of skill set anticipated from an engineering graduate from the employer’s perception, and reveal the existing competency gaps for successful execution of engineering services.